(untitled) (Superficies y Vacío, 2013)
Thin films of PbTiO3 were deposited at a temperature of 400°C onto Pt/Ti/SiO2/Si <100> substrates by the aerosol assisted CVD method using organometallic precursors. With the purpose of stabilizing and homogenizing the Perovskite phase, the films were annealed at 550°C, in a Pb-rich atmosphere, for 12 h. Thermogravimetric analysis of the precursors were performed to determine the theoretical temperature of deposition. The crystallinity of the phase before and after annealing was characterized by grazing incidence x-ray diffraction. Additionally, microstructural analysis using scanning (SEM) and transmission (TEM) electron microscopy was also performed.